Kedudukan Peralihan Hak atas Objek Jaminan Fidusia tanpa Persetujuan Lessor (Studi Putusan Nomor 25/Pid.B/2024/PN KTG) - Feisal Al Jufri Aryul; Saidin; hasim purba; suprayitno (CV Rewang Rencang, 2025)
In leasing practice, transfer of fiduciary collateral objects to third parties occurs through informal agreements where payment obligations may shift between parties. This normative juridical research employs qualitative library study methodology to produce descriptive-analytical findings. The study examines three critical aspects: first, the legal position of transferring fiduciary security rights without lessor consent, which violates the Fiduciary Security Law requiring written authorization; second, legal protection mechanisms for lessors through civil and criminal liability provisions; and third, lessee accountability under Decision Number 25/Pid.B/2024/PN Ketapang, where the court correctly determined the defendant fulfilled criminal elements under Article 36 of the Fiduciary Security Law for transferring secured objects without prior written fiduciary receiver consent.